2017
DOI: 10.1590/0034-7167-2016-0406
|View full text |Cite
|
Sign up to set email alerts
|

Insulin therapy waste produced in the households of people with diabetes monitored in Primary Care

Abstract: Objective: To analyze the insulin therapy waste disposal produced in the households of people with diabetes mellitus (DM). Method: Cross-sectional study with 105 Primary Care patients. Socio-demographic and clinical variables and insulin therapy practice were analyzed through the absolute and relative frequencies, Fisher's exact test and prevalence ratio (PR). Results: The association between types of insulin (60.0%), administered with a disposable syringe attached to a needle (80.9%), and a high percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 13 publications
5
21
0
15
Order By: Relevance
“…Patients who were educated about sharp disposal were likely to dispose of them “safely”. This finding is also supported by several other studies [3, 8, 9, 16, 17]. When all safe methods of sharps disposal are reviewed, there were no relationships between age, gender or type of diabetes.…”
Section: Discussionsupporting
confidence: 84%
“…Patients who were educated about sharp disposal were likely to dispose of them “safely”. This finding is also supported by several other studies [3, 8, 9, 16, 17]. When all safe methods of sharps disposal are reviewed, there were no relationships between age, gender or type of diabetes.…”
Section: Discussionsupporting
confidence: 84%
“…Regarding the disposal of sharps, approximately half of the older people discarded sharps in a hard flask and only half of them performed the procedure properly. Similar results were found in a recent study conducted in the city of Fortaleza, CE, Brazil, which showed that 57.1% of the participants discarded in an inappropriate manner the waste generated by the administration of insulin in the ordinary household waste, even though they had been instructed on the appropriate manner to perform the disposal of this material 13 . International studies 32 - 33 also found high percentages of inappropriate waste disposal resulting from insulin therapy, and the possible reason for this finding was the unsatisfactory impact of continuing education on the safe disposal of sharps.…”
Section: Discussionsupporting
confidence: 88%
“…The epidemiological aspects of DM have been extensively studied 1 , 12 , whereas there is a lack of information on self-administration of insulin, especially in older people. Previous studies at national level have identified frequent errors in the preparation and administration of insulin 10 , as well as improper disposal of residues generated by the administration of insulin at home 13 . This reality is not restricted only to Brazil, being also highlighted in studies at international level 14 - 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Educational reinforcement is needed to change this practice and to present the appropriate disposal of these materials in order to comply with the recommendations and to provide safe waste (1) . In this sense, other national studies also obtained similar results in relation to the disposal of sharps (20)(21) .…”
Section: Discussionsupporting
confidence: 69%